Postoperative adjuvant radiochemotherapy with cisplatin versus adjuvant radiochemotherapy with cisplatin and pembrolizumab in locally advanced head and neck squamous cell carcinoma- the study protocol of the Adrisk trial - Wiegand, Susanne; Wichmann, Gunnar; Vogt, Jeannette; Vogel, Kathrin; Franke, Annegret; Kuhnt, Thomas; Lordick, Florian; Scheuble, Anne-Marie; Hambsch, Peter; Brossart, Peter; Bauernfeind, Franz Georg; Kaftan, Holger; et al. (Frontiers in Oncology, 2023)
Most of the patients with head and neck squamous cell carcinoma (HNSCC) are diagnosed with locally advanced disease. Standards of care for curative-intent treatment of this patient group are either surgery and adjuvant radio(chemo)therapy (aRCT) or definitive chemoradiation. Despite these treatments, especially pathologically intermediate and high-risk HNSCC often recur. The ADRISK trial investigates in locally advanced HNSCC and intermediate and high risk after up-front surgery if the addition of pembrolizumab to aRCT with cisplatin improves event-free sur-vival compared to aRCT alone. ADRISK is a prospective, randomized controlled investiga-tor-initiated (IIT)-phase II multicenter trial within the German Interdisciplinary Study Group of German Cancer Society (IAG-KHT). Patients with primary resectable stage III and IV HNSCC of the oral cavity, oropharynx, hypopharynx and larynx with pathologic high (R1, extracapsular nodal extension) or intermediate risk (R0 <5 mm; N≥2) after surgery will be eligible. Two hun-dred forty patients will be randomly assigned (1:1) to either standard aRCT with cisplatin (standard arm) or aRCT with cisplatin + pembrolizumab (200 mg iv, in 3-week cycle, max. 12 months) (interventional arm). Endpoints are event-free and overall survival. Recruitment started in August 2018 and is ongoing.